Derivation of state and output equations for systems containing switches and a novel definition of a switch using the bond graph model - Demir, Y; Poyraz, M; Koksal, M (Pergamon-Elsevier Science Ltd, 1997)
This Study gives a novel switch definition which is at the same time simple and more general. In addition, a formulation giving state and output equations is presented by using the bond graph model of switch-containing systems. The use of a computer program called BONDSO is described and examples of the application are given. Copyright (C) 1997 Published by Elsevier Science Ltd.